2021
DOI: 10.1016/j.jsams.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and adapting endurance training on the basis of heart rate variability monitored by wearable technologies: A systematic review with meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
0
19
0
10
Order By: Relevance
“…Such decisions are made based on changes above and below threshold values, constructed at an individual level. Indeed in a recent systematic review and meta-analysis [ 47 ], it was shown that, across eight studies, HRV-guided training had a significant, medium-sized positive effect on the improvement of sub-maximal physiological parameters. Furthermore, there were fewer non-responders to HRV-guided training, meaning that the use of this approach induced more consistent favorable effects.…”
Section: Discussionmentioning
confidence: 99%
“…Such decisions are made based on changes above and below threshold values, constructed at an individual level. Indeed in a recent systematic review and meta-analysis [ 47 ], it was shown that, across eight studies, HRV-guided training had a significant, medium-sized positive effect on the improvement of sub-maximal physiological parameters. Furthermore, there were fewer non-responders to HRV-guided training, meaning that the use of this approach induced more consistent favorable effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a monitoring purpose the usage of DFA a1 may help inform an athlete about their recovery from previous training sessions. It has become commonplace for individuals to monitor and track resting HRV as a method to direct daily exercise intensity and volume ( Granero-Gallegos et al, 2020 ; Düking et al, 2021 ). Unfortunately, resting HRV requires a regular day-to-day monitoring routine including standardization (e.g., time of day, nutrition; Bellenger et al, 2016 ) and logistically may not fit into an irregular schedule.…”
Section: Can Dfa A1 Be Used As An Index Of Fatigue Daily Training Gui...mentioning
confidence: 99%
“…Preliminary data is suggestive ( Rogers et at., 2021f ), but additional research is needed. Prospective training intervention studies of participants who utilize knowledge of DFA a1 behavior during the early stage of routine exercise sessions for training guidance (as shown in monitoring with time domain HRV values during rest conditions ( Düking et al, 2021 )) would be of great interest as a tool to determine daily “readiness to train”.…”
Section: Future Directionsmentioning
confidence: 99%
“…En pacientes con EPOC ha sido útil a la hora de determinar la actividad física en los programas de rehabilitación respiratoria y en la predicción de exacerbaciones [51]. A nivel cardiaco los dispositivos portátiles comerciales son precisos para medir los pasos y la frecuencia cardíaca [52].…”
Section: Telemonitorizaciónunclassified